Sexual offences and corroboration / Mohd. Fadzil Mohd. Khalil - Mohd. Khalil, Mohd. Fadzil (Faculty of Law, 1985)
Sexual offences are offences acted against the human body of the victim, in the act of sexual lust. It is generally assumed that many of the sexual offences such as rape can only be committed as perpetrators by males but even in the other offences the offenders are predominently male. Corroboration is a form of evidence which would confirm or strengthen the evidence or testimony given by a witness. In sexual cases where the victim is also the witness, the law of corroboration plays an important role in supporting or confirming the testimony of the witness against the accused. In trying the person, accused to have committed the sexual offence, the relationship between sexual cases and the law of corroboration is inevitable. This relationship seems to lead to the argument, for and against the need for the corroboration of the evidence of the complainant or victim in sexual offence cases